Tracheal rupture: a rare complication related to foreign body aspiration - Çelebioğlu, Bilge; Tanyel, F. Cahit; Altunkaya, Hanife (The Turkish Journal of Pediatrics, 1999)
A one-year-old patient admitted following foreign body aspiration and referred following cardiopulmonary resuscitation in a local hospital was diagnosed to have tracheobronchial rupture. We first assumed puncture of the mucous membrane of the left main bronchus by the tip of the tube. Later, we thought that the rupture might have been caused by rigid bronchoscopy. Etiology and treatment are discussed and recent literature reviewed.